2016
DOI: 10.17691/stm2016.8.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Strength Properties of Abdominal Wall in Intraperitoneal and Retromuscular Repair Using Lightweight and Ultra-Lightweight Synthetic and Titanium-Containing Endoprostheses (Experimental Study)

Abstract: The application of ultra-lightweight materials for abdominal wall hernia repair has not been controlled so far, and the capabilities of synthetic and titanium-containing endoprostheses, as well as the peculiarities and possible differences in connective tissue development in an implantation area are not adequately investigated.The aim of the investigation was to study in experiment strength properties of connective tissue formation in the area of synthetic and titanium-containing endoprostheses implanted durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…On the territory of Russia and eastern countries, titanium mesh implants made of ultrathin titanium filaments have become common. A number of experimental studies have shown their advantages compared with polymer mesh implants (Parshikov, Kazantsev, et al, 2016; Parshikov, Mironov, et al, 2016; Kazantsev et al, 2016; Ovchinnikov, Uchevatkina, Kurbatova, Lukyanenko, & Yakutina, 2019). Currently, titanium mesh implants for hernia repair are being studied in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…On the territory of Russia and eastern countries, titanium mesh implants made of ultrathin titanium filaments have become common. A number of experimental studies have shown their advantages compared with polymer mesh implants (Parshikov, Kazantsev, et al, 2016; Parshikov, Mironov, et al, 2016; Kazantsev et al, 2016; Ovchinnikov, Uchevatkina, Kurbatova, Lukyanenko, & Yakutina, 2019). Currently, titanium mesh implants for hernia repair are being studied in clinical trials.…”
Section: Introductionmentioning
confidence: 99%